Analisis Strategis STMIK Bina Bangsa Kendari melalui Pendekatan EFAS dan IFAS - Inggi, Rahmat; Umar, Sutriasi; Mokodompit, Eliyanti Agus (Sekolah Tinggi Ilmu Ekonomi AMM, 2025)
This study aims to analyze the strategic position of STMIK Bina Bangsa Kendari using the Internal Factors Analysis Summary (IFAS) and External Factors Analysis Summary (EFAS) frameworks, which serve as the basis for determining the institution’s placement within the Internal–External (IE) Matrix. A descriptive quantitative approach was employed, with data collected through documentation reviews, structured interviews, and field observations involving institutional leaders, lecturers, administrative staff, and students. The IFAS analysis produced a score of 2.50, indicating a moderate internal condition characterized by strengths in lecturer competencies, curriculum relevance, and the implementation of digital academic systems. However, weaknesses were found in laboratory facilities, administrative processes, and financial dependence. Meanwhile, the EFAS score of 2.60 reflects a reasonably strong response to external opportunities such as digital industry growth, government policies on educational transformation, and technological advancements, despite challenges related to competition and regulatory demands. Synthesizing both scores place the institution in the Hold and Maintain quadrant of the IE Matrix, highlighting the need for internal consolidation before pursuing more aggressive growth strategies.